Faʿāliyatu Taqniyati "T-N-K" fī Taʿlīmi al-Kitābah li-Tarqiyati Qudrati al-Tafkīri al-Ibdāʿī - Siti Nur Istianah; Erta Mahyudin; Siti Uriana Rahmawati (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to examine the effectiveness of the “TNK” (Think, Publish, Write) technique in improving students’ creative thinking skills in writing at MTs Negeri 2 Jakarta. Using a quantitative quasi-experimental design, the research involved two groups: an experimental group taught using the TNK technique and a control group taught using conventional methods. Data were collected through pre-test and post-test assessments, focusing on four dimensions of creative thinking in writing: fluency, flexibility, originality, and elaboration. The findings revealed that the experimental group achieved a post-test mean score of 79, significantly higher than the control group’s mean score of 54. The independent sample t-test result (t = 7.621) exceeded the critical values at both 5% and 1% significance levels, indicating a significant effect of the TNK technique. The N-Gain score of 0.52 suggested a moderate level of effectiveness. These results indicate that the TNK technique offers a structured yet creative learning environment, enabling students to express ideas more freely, enhance critical thinking, and develop better writing skills. The study recommends adopting the TNK technique as an alternative instructional strategy for teaching writing.